Building local research capacity through time, trust and knowledge transfer - Desai, Bina; Olomu, Rukeme (2025)
This third contribution to our blog series frames mentoring modality as a pathway to equal access. Hybrid design is more than a logistical choice, it actively lowers barriers for women, caregivers, and researchers outside capital cities and regional hubs. The African Climate Mobility Academy (ACMA) model combines minimal in-person convenings with sustained online engagement to widen access, reduce travel burdens, and preserve quality. The result is a design that is replicable across contexts and disciplines. Local hubs hosted by universities or research centers, global mentor pools, and structured online peer review provide reliable and regular guidance for mentees. A growing alumni community comprising both mentors and mentees becomes the impact multiplier. But a core question shapes any hybrid learning architecture: Which outcomes require in-person interaction, which can be delivered online, and which benefit from both?